Systemic administration of β-glucan of 200 kDa modulates melanoma microenvironment and suppresses metastatic cancer. (1st February 2018) - Zhang, Mei; Chun, Liane; Sandoval, Victor; Graor, Hallie; Myers, Jay; Nthale, Joseph; Rauhe, Peter; Senders, Zachary; Choong, Kevin; Huang, Alex Y.; Kim, Julian
ABSTRACT: Converting an immunosuppressive melanoma microenvironment into one that favors the induction of antitumor immunity is indispensable for effective cancer immunotherapy. In the current study we demonstrate that oat-derived β-(1-3)-(1-4)-glucan of 200 kDa molecular size (BG34-200) previously shown to mediate direct interaction with macrophages could alter the immune signature within melanoma microenvironment. Systemic administration of BG34-200 resulted in reversion of tolerant melanoma microenvironment to an immunogenic one that allows M1-type activation of macrophages, the induction of pro-inflammatory cytokines/chemokines including IFN-γ, TNF-α, CXCL9, and CXCL10, and enhanced IRF1 and PD-L1 expression. In turn, BG34-200 induced a superior antitumor response against primary and lung metastatic B16F10 melanoma compared to untreated controls. The enhanced tumor destruction was accompanied with significantly increased tumor infiltration of CD4 + and CD8 + T cells as well as elevated IFN-γ in the tumor sites. Systemic administration of BG34-200 also provoked systemic activation of tumor draining lymph node T cells that recognize antigens naturally expressing in melanoma (gp100/PMEL). Mechanistic studies using CD11b-knockout (KO), CD11 c-DTR transgenic mice and nude mice revealed that macrophages, DCs, T cells and NK cells were all required for the BG34-200-induced therapeutic benefit. Studies using IFN-γ-KO transgenic mice showed that IFN-γ was essential for the BG34-200-elicited antitumor response. Beyond melanoma, the therapeutic efficacy of BG34-200 and its immune stimulating activity were demonstrated in a mouse model of osteosarcoma. Together, BG34-200 is highly effective in modulating antitumor immunity. Our data support the potential therapeutic use of this novel immune modulator in the treatment of metastatic melanoma.